2018
DOI: 10.1177/0042085918756715
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Mexican American Immigrant Students on the Border: A Case Study of Culturally Responsive Leadership in a Dual Language Elementary School

Abstract: Mexican American students constitute the largest group of Latina/os in the United States and have been subjected to a number of educational and social injustices, particularly with relation to how their cultural and linguistic assets are viewed within public schools. This qualitative case study considers culturally responsive leadership in a Mexican American immigrant community and examines two primary research questions: (a) What principal actions support creating a culturally responsive school partly through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…She grew up as the daughter of a white educator in New Zealand, but spent time teaching in a very multiethnic, multicultural school in London. This started a process, for her, of reflection; acknowledgement that there were many other people in the world who understood their world differently than she did, and de-centering whiteness (DeMatthews & Izquierdo, 2018). What followed was a sense of humility as a Pākehā person in a predominantly Māori community returning to live into New Zealand to work.…”
Section: Resultsmentioning
confidence: 99%
“…She grew up as the daughter of a white educator in New Zealand, but spent time teaching in a very multiethnic, multicultural school in London. This started a process, for her, of reflection; acknowledgement that there were many other people in the world who understood their world differently than she did, and de-centering whiteness (DeMatthews & Izquierdo, 2018). What followed was a sense of humility as a Pākehā person in a predominantly Māori community returning to live into New Zealand to work.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified leadership practices that support the learning of Hispanic English learners, including knowledge of effective pedagogical practices to ensure English learners develop their English language skills and have access to rich curriculum content (DeMatthews and Izquierdo, 2020; Gersten and Baker, 2000; Masumoto and Brown-Welty, 2009; Murakami et al. , 2012; Scanlan and Lopez, 2012).…”
Section: Literature Review and Frameworkmentioning
confidence: 99%
“…Nevertheless, evidence suggests that in some schools serving significant numbers of Hispanic students, leaders were able to make a difference (DeMatthews and Izquierdo, 2020; Grothaus et al. , 2010; Klar and Brewer, 2013; McGee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the experiences of immigrant teachers reveals the importance of focusing on their role as key players in the education of immigrant children (Ratkóvic and Pietka-Nykasa, 2016). In addition to that existing scholarship suggests that connections with colleagues and supportive relationships with school leaders are especially meaningful for dual-language immigrant teachers (DeMatthews & Izquierdo, 2020;Fee, 2011).…”
Section: Constrained Carementioning
confidence: 99%